Spectroscopic signatures of extra-tidal stars around the globular clusters NGC 6656 (M22), NGC 3201 and NGC 1851 from RAVE - Kunder, Andrea; Grebel, Eva K.; Boeche, Corrado (Astronomy and astrophysics, 2014)
Context. Stellar population studies of globular clusters have suggested that the brightest clusters in the Galaxy might actually be the remnant nuclei of dwarf spheroidal galaxies. If the present Galactic globular clusters formed within larger stellar systems, they are likely to be surrounded by extratidal halos and/or tails made up of stars that were tidally stripped from their parent systems. Aims. The stellar surroundings around globular clusters are therefore one of the best places to look for the remnants of an ancient dwarf galaxy. Here an attempt is made to search for tidal debris around the supernovae enriched globular clusters M 22 and NGC 1851, as well as the kinematically unique cluster NGC 3201. Methods. The stellar parameters from the RAdial Velocity Experiment (RAVE) are used to identify stars with the RAVE metallicities, radial velocities, and elemental abundances that are consistent with the abundance patterns and properties of the stars in M 22, NGC 1851, and NGC 3201. Results. Discovery of RAVE stars that may be associated with M 22 and NGC 1851 are reported, some of which are at projected distances ~10 degrees away from the core of these clusters. Numerous RAVE stars associated with NGC 3201 suggest that either the tidal radius of this cluster is underestimated or that there are some unbound stars extending a few arc minutes from the edge of the cluster’s radius. No other extratidal stars associated with NGC 3201 could be identified. The bright magnitudes of the RAVE stars make them easy targets for high-resolution follow-up observations, eventually allowing further chemical tagging to solidify (or exclude) stars outside the tidal radius of the cluster as tidal debris. In both our radial velocity histograms of the regions surrounding NGC 1851 and NGC 3201, a peak of stars at ~230 km s-1 is seen, consistent with extended tidal debris from ω Centauri.
Gesehen am 23.10.2020